2020
DOI: 10.1108/jfm-07-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

The role of facilities management in green retrofit of existing buildings in the United Arab Emirates

Abstract: Purpose Green retrofitting is acknowledged as an essential strategy toward achieving long-term sustainability in the built environment. To implement this strategy successfully, the role of facility managers cannot be ignored. The purpose of this paper is to investigate present practices that are used in managing the existing facilities, to highlight the elements that govern the process of green retrofitting, and discuss the efforts and contribution of facility managers in enhancing the environmental performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Responsible for managing both buildings and the relevant stakeholders (e.g., owners, occupants, tenants), FM practitioners have to communicate with retrofitting decision makers and facility users, modify facilities, upgrade systems for energy use, and develop mechanisms for measuring energy consumption, monitoring energy use process, and assessing energy performance [34,35]. Thus, FM practitioners play critical roles in supporting decision making on building retrofits, and their opinions on KPIs for building retrofit performance are useful.…”
Section: The Role Of Fm Practitionersmentioning
confidence: 99%
“…Responsible for managing both buildings and the relevant stakeholders (e.g., owners, occupants, tenants), FM practitioners have to communicate with retrofitting decision makers and facility users, modify facilities, upgrade systems for energy use, and develop mechanisms for measuring energy consumption, monitoring energy use process, and assessing energy performance [34,35]. Thus, FM practitioners play critical roles in supporting decision making on building retrofits, and their opinions on KPIs for building retrofit performance are useful.…”
Section: The Role Of Fm Practitionersmentioning
confidence: 99%
“…Furthermore, it is a discipline that comprises strategic and tactical operations (Asbollah, Isa, & Kamaruzzaman, 2016). In terms of technical competence, FM can improve the sustainability of existing buildings and reduce their environmental impact through a 'green retrofit' process (Mawed, Mahmoud;Tilani, Vinay;Hamani, Karima, 2019). Asia & Africa is still seen as a newcomer in the sector, compared to Europe and the USA, in facilities management (Sari, 2018).…”
Section: Benefits For Sustainable Retrofittingmentioning
confidence: 99%
“…A study found that the performance outcomes of the logic model can help the residents and management to have a deep understanding in the current performance of their residential building and help to develop strategies to enhance safety and health of the residential buildings in future. Most of the considerations are related to the performance of facility management, as can be found in [14]. Consideration of the appearance and performance of communal space is also highlighted by [15].…”
Section: The Performance Evaluation Of Property Management Companies mentioning
confidence: 99%
“…Based on the study, the project can be evaluated based on 16 criteria that are grouped under four categories, which are economic, environmental, physical and social. Similar to [14], this study also measured the satisfaction of residents toward the building's facilities. It was also found that residents prefer to live in a new apartment compared to the old apartment, because of the attractive facilities, particularly the green communal space.…”
Section: Estimation For Predicting the Performance Of Private Apartmementioning
confidence: 99%